Analisis pengaruh faktor internal bank dan eksternal terhadap Non-Performing Financing (NPF) pada Bank Perkreditan Rakyat Syariah di Indonesia - Rindang Nuri Isnaini Nugrohowati; Syafrildha Bimo (Faculty of Economics, Universitas Islam Indonesia, 2019)
This study aims to determine the internal and macroeconomic factors that influence Non-Performing Financing (NPF) of BPRS (Sharia Rural Banks) in Indonesia. Data analysis method used in this study is panel data regression by taking a sample of 54 BPRS from 2012 to 2017 biannually. The results of this study show that toward NPF of BPRS in Indonesia, the variable of Total Asset has no significant effect, CAR and ROA have a negative and significant effect, while OER has a positive and significant effect. Meanwhile, the macroeconomic variables of BI Rate and PDRB have a positive and significant effect toward NPF of BPRS in Indonesia. Lastly, the variables of inflation and unemployment have no effect toward NPF of BPRS in Indonesia.